FEMINISM IN ENOLA HOLMES FILM: A SEMIOTIC LENS - Syahriyani, Alfi; Novikasandra, Maidhotul Kaifa (Elite : English and Literature Journal, 2022)
Film is not merely a medium to entertain but also a reflection of society's values and conditions. This research deals with the portrayal of feminism in the film of Enola Holmes in the era of 19th century through its main character of the film ‘Enola’. It uses the qualitative method by employing the theory of semiotics of Charles Sanders Peirce, which categorizes signs into three related parts, namely representamen, object, and interpretant. The data was taken by identifying and interpreting the signs through the scenes of the films, including icon, index, and symbol. The findings show that the film represents the feminist values through the character of Enola, such as independent, intellectual, showing freedom of choice, gender equality, and right to privacy. The character challenged the social norms in the 19th century, which still positioned women as inferior social beings and were oppressed by the patriarchal system. The film also brings relevant messages as it also indirectly criticizes the present women issues through the historical lens.